Identifying The Working Process Of Automatic Fish Feed Tool Based On Arduino Uno - Nur Hartawati, Ertie (International Journal of Science, Technology & Management, 2021)
This Arduino-Based Automatic Fish Feeding Tool is a tool that serves to make it easier to care for fish in the aquarium, especially the feeding. The purpose of making this automatic fish feed tool is to explain about the automatic fish feed tool. The ability of this tool is that it can provide feed automatically with the given time plan is feeding 2 times a day and for the amount of feed dose adjusted to the number of servo motor rotations, namely 1 rotation of 150?, resulting in a feed dose of 10 Grams. With the working method using the Arduino IDE application and with the Arduino Uno working system, a command coding is given which is combined with the Uno shield board then jumper to the RTC DS3231 so that it can show the time very accurately and update the time data in real time.